Analysis of Microscopy and RDT Performance in Detecting Malaria Among Suspected Patients at Arso III Health Center - Hartati, Risda; Ap, Ema Elvira Alwina; Asrianto; Sahli, Indra Taufik; Kurniawan, Fajar Bakti; Wardani, Afika Herma; Purwati, Rina (Jurnal Kedokteran Universitas Palangka Raya, 2025)
Malaria remains a significant public health problem in Papua. Keerom is one of the districts with a high incidence of malaria. This study aims to evaluate the performance of the Rapid Diagnostic Test (RDT) in comparison to microscopic examination, the gold standard for malaria diagnosis. This descriptive analytic study involved 40 suspected malaria patients at Arso III Health Center, Skanto District, Keerom Regency, Papua. Blood samples were examined using thick blood smears, thin blood smears, and the Care Start RDT. The study employed a cross-sectional design with purposive sampling. Microscopic examination identified five positive cases, corresponding to 12.5 percent, while the RDT detected nine positive cases, representing 22.5 percent of the total. The diagnostic analysis of the RDT revealed a sensitivity of 100 percent, a specificity of 88.6 percent, a positive predictive value of 55.6 percent, and a negative predictive value of 100 percent. The McNemar test showed a significant difference, p = 0.046. RDT proved reliable for excluding malaria, as no false-negative results were found. However, positive results require confirmation by microscopy or PCR to avoid misidentification and treatment errors.